State of the union [videorecording (DVD)] - Capra, Frank, 1897-1991; Tracy, Spencer, 1900-1967; Hepburn, Katharine, 1907-2003; Johnson, Van, 1916-2008; Lansbury, Angela, 1925-; Lindsay, Howard, 1889-1968; Crouse, Russel, 1893-1966 (Universal Studios Home Entertainment, 2011)
Spencer Tracy stars as an idealistic industrialist who runs for the presidency. Based on a Pulitzer Prize-winning play by Howard Lindsay and Russel Crouse.